2018
DOI: 10.3892/mco.2018.1589
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial meningioma as primary presentation for an undiagnosed collision metastatic breast cancer: Case report and literature review

Abstract: Intracranial metastasis from breast cancer is a relatively common finding, however, the appearance of breast cancer metastasis in a meningioma is very rare. Several cases of tumor-to-tumor metastasis and collision tumors have been reported previously, with meningioma being implicated as the most common benign intracranial neoplasm to harbour the metastasis. Occasionally, the discovery of a tumor-to-meningioma metastasis may herald the diagnosis of an occult primary malignancy. Careful histopathological assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is sometimes confused with a collision tumor, which possesses similar characteristics as TTM. It is crucial to differentiate TTM from a collision tumor, which refers to the presence of two histologically distinct tumors within an anatomic location with infiltration of the tumors into one another [ 5 6 7 ]. Syed et al [ 7 ] reported that understanding the distinction between a collision tumor and TTM is necessary to plan the surgical approach and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is sometimes confused with a collision tumor, which possesses similar characteristics as TTM. It is crucial to differentiate TTM from a collision tumor, which refers to the presence of two histologically distinct tumors within an anatomic location with infiltration of the tumors into one another [ 5 6 7 ]. Syed et al [ 7 ] reported that understanding the distinction between a collision tumor and TTM is necessary to plan the surgical approach and management.…”
Section: Discussionmentioning
confidence: 99%
“…Most intra-meningioma metastases are diagnosed histopathologically, and they cannot be accurately diagnosed using CT or MRI. Furthermore, it is difficult to differentiate TTM from a collision tumor using MRI [ 5 ]. However, MRI may be used to identify rapid growth, peritumoral edema, irregular margins, mushroom pattern, and heterogeneous enhancement, which have been reported previously [ 7 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative oncological treatment depended on the type of malignant tumour, type of spread and of course general and oncological state of a patient. Some patients died before starting any oncological treatment, radiotherapy or chemotherapy [12,17,22,28,49,59].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, conditions such as protection of tumoral tissue from immune surveillance, decreased expression of the tumor suppressor genes, and the existence of cellular and hormonal signaling could potentially play a role in tumor-to-meningioma metastasis. [ 6 , 12 , 14 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Limitation of routine imaging workups like CT or MRI in differentiation between these possible diagnoses affirms the importance of careful pathological analysis as the tumor-to-tumor metastasis could be missed if the whole tumor is not carefully sampled. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%